Antimalarial Activity of Azadipeptide Nitriles - Löser, Reik (2009)
Azadipeptide nitriles – novel cysteine protease inhibitors – display structure-dependent antimalarial activity against both chloroquine-sensitive and chloroquine-resistant lines of cultured Plasmodium falciparum malaria parasites. Inhibition of parasite’s haemoglobin-degrading cysteine proteases was also investigated, revealing the azadipeptide nitriles as potent inhibitors of falcipain-2 and -3. A correlation between the cysteine protease-inhibiting activity and the antimalarial potential of the compounds was observed. These first generation azadipeptide nitriles represent a promising new class of compounds for antimalarial drug development.